Cytomegalovirus infection in Systemic Lupus Erythematosus: report of four cases challenging the management of the disease, and literature review. (March 2019) - Sebastiani, G.D.; Iuliano, A.; Canofari, C.; Bracci, M.
Cytomegalovirus (CMV) is particularly dangerous in systemic lupus erythematosus (SLE), being a problem both for the differential diagnosis with disease flare and for the management of SLE flare with immunosuppressive drugs. We report on four cases of SLE with concomitant CMV infection, having some common clinical and laboratory characteristics. Our data suggest that lupus patients presenting with symptoms such as fever, diarrhea, and respiratory symptoms, alone or in combination, and laboratory evidence of leukopenia, elevated transaminases, and hyponatremia, especially in the setting of recent immunosuppressive treatments, should be screened for CMV.